Increasing The Level Of Innovative Mobility Of Educators In The Conditions Of Digital Transformation As A Pedagogical Problem - Lауlо Bаgbеkоvа (Genius Journals, 2025)
The processes of digital transformation represent one of the key factors shaping the modern education system, introducing profound changes to the content, forms, and methods of pedagogical activity. In turn, this raises the issue of enhancing teachers’ innovative mobility as a pressing pedagogical challenge. This article analyzes the necessity of developing teachers’ professional competencies under conditions of digital transformation, increasing their adaptability to changing circumstances, mastering new pedagogical technologies, and effectively integrating them into the educational process.
Keywords: digital transformation; innovative mobility; pedagogical competence; professional development